Prevalence Of Physical Activity, Sedentary Behaviour And Unhealthy Dietary Habits Among Moroccan Adolescents (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Adolescence represents a very crucial phase in the human life cycle. During this period adolescents develop individual lifestyle habits. as a result, and in the absence of data concerning the above characteristics, in the Beni Mellal-Khénifra region, we leaded a cross-sectional survey of growth ,food and hygiene behaviour conducted among a sample of 812 adolescents, including 404 boys attending school aged 13 to18 years, Furthermore, the objective of this study was also to verify among college students of the region the prevalence of moderate physical activity levels, unhealthy dietary habits and sedentary behaviour, in order to determine the risk factors related to the physical inactivity. The prevalence of physical activity was 36.08% (50.0% among boys and 22.06% among girls). Nearly 40% of these adolescents spend more than 2 hours a day in front of the screens. Unhealthy dietary habits are more frequent among adolescents and the majority of them consume Fried potatoes (fries and chips) Doughnuts/cake, Sugary drinks more than three times a week. These results show significant associations between physical activity, sedentary habits and some unhealthy dietary habits.